2013
DOI: 10.1016/j.neuro.2013.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Effects of eribulin, vincristine, paclitaxel and ixabepilone on fast axonal transport and kinesin-1 driven microtubule gliding: Implications for chemotherapy-induced peripheral neuropathy

Abstract: Chemotherapy-induced peripheral neuropathy (CIPN) is a serious, painful and dose-limiting side effect of cancer drugs that target microtubules. The mechanisms underlying the neuronal damage are unknown, but may include disruption of fast axonal transport, an essential microtubule-based process that moves cellular components over long distances between neuronal cell bodies and nerve terminals. This idea is supported by the “dying back” pattern of degeneration observed in CIPN, and by the selective vulnerability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
155
0
6

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 197 publications
(167 citation statements)
references
References 61 publications
(106 reference statements)
6
155
0
6
Order By: Relevance
“…The incidence of paclitaxel-induced neuropathy ranges from 20% to 70% of patients (24,25). Mechanisms include disruption of axonal transport (26,27), mitochondrial damage (28)(29)(30), altered ion channel activities (31), and neuronal inflammation (32,33). Here we screened three compound libraries, including ion channel ligands, GABA and REDOX libraries, for the discovery of potential neuroprotective drugs.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of paclitaxel-induced neuropathy ranges from 20% to 70% of patients (24,25). Mechanisms include disruption of axonal transport (26,27), mitochondrial damage (28)(29)(30), altered ion channel activities (31), and neuronal inflammation (32,33). Here we screened three compound libraries, including ion channel ligands, GABA and REDOX libraries, for the discovery of potential neuroprotective drugs.…”
Section: Discussionmentioning
confidence: 99%
“…33 Based on the reported evidence of changes in tubulin dynamics obtained in different cellular systems and on the relevance of tubulin interference in the pathogenesis of toxic peripheral neuropathies, 21,34,35 we focused on α-tubulin polymerization as a possible mechanism of neurotoxicity in BiPN. Despite the fact that the severity of nerve damage was more marked in the caudal nerve than the sciatic nerve, we selected the latter tissue to assay proteasome inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…La Pointe et al have demonstrated an inhibition of microtubule-based fast axonal transport as significant contributor to neurotoxicity induced by microtubule-targeting drugs, including taxanes, through different mechanisms [23]. In this in vitro study, eribulin mesylate (a synthetic macrocyclic ketone analogue of the marine sponge natural product halichondrin B) and paclitaxel both inhibit anterograde fast axonal transport but don't inhibit retrograde fast axonal transport (cytoplasmic dynein-dependent), in contrast to vincristine and ixabepilone (an epothilone that stabilizes the microtubules).…”
Section: Pathophysiological Mechanismsmentioning
confidence: 99%